RODWELL, G. (2020). Politics and the Mediatization of School Educational Policy. The dog-whistle dynamic, New York: Routledge, 222 pp. - Mas de Sanfélix, Ana (Daimon Revista Internacional de Filosofia, 2022)
Reseña de: RODWELL, G. (2020). Politics and the Mediatization of School Educational Policy. The dog-whistle dynamic, New York: Routledge, 222 pp.